Mosquito Nets Installation in Livestock Sheds as a Basis of Accelerated Malaria Vector Control Development - Santjaka, Aris; Sunaryo, Sunaryo; Anwar, M. Choiroel; Utomo, Nur; Firdaust, Mela; Cahyono, Tri; Indro Wardono, Hari Rudijanto; Amaliah, Nurul; Husnul Yusmianti, Siti Nur; Tauleka, Abdul Rohim; Yudastuti, Ririh; Wahjuni, Chatarina Umbul (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
The decrease in the incidence of malaria has only reached 66.67%, from the target of 90% in 2030; Anopheles spp mosquitoes are zoophilic, So mosquitoes are more numerous in cattle sheds. The research is intended to change vector control policies by considering livestock sheds to accelerate malaria elimination. This study was a Pre-experiment with the design of the static group comparison, mosquito capture used a spot survey of six houses; three houses have goat sheds and three cowshed houses; mosquito catching with WHO guidelines that one house there are two catchers; likewise in cattle sheds. Arrests were made all night from 06.00 pm-06.00 am. The results, the ratio of Anopheles spp mosquitoes caught in livestock sheds is 36.5 times more than at home; while the vector is 2.5 more. The results of the statistical analysis are significant (p=0,000). Livestock sheds can be used as an alternative to malaria vector control to accelerate the decrease in density so that the incidence of malaria also decreases.